ABDULLAH NASHIH ULWAN’S PERSPECTIVE OF CHILD EDUCATION CONCEPTS AND ITS RELEVANCE TO RELIGIOUS CHARACTER FORMATION IN THE FAMILY ENVIRONMENT - Muhammad Isnaini; Putri Rika Amelia; Novia Ballianie (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
Religious character is one of the 18 aspects of character values according to the Indonesian Ministry of Education and Culture, which ranks first. Its position in the first order illustrates that this character is an essential character that children must possess in line with the concept of child education in Islam in Abdullah Nashih Ulwan's view. Abdullah Nashih Ulwan is a Muslim figure who plays an active role in da'wah and Islamic education. He argues that proper character education directs humans to have good personalities who hold fast to the values of faith in Allah SWT and realize that Allah SWT is always watching over them. Religious character is the character, character, or personality of a person who is closely related to God and is based on the teachings of the religion he adheres to. This study aims to analyze the concept of children's education in Islam from the perspective of Abdullah Nashih Ulwan. Then the concept he explained was relevant to forming religious characters in the family environment. This study uses library or library research with a content analysis approach or content analysis, then collects data and draws conclusions from the research results. This study concludes that the concept of children's education in Islam in Abdullah Nashih Ulwan's view is closely related to the formation of religious characters in the family environment. Awareness of parents in carrying out the responsibilities of faith, morals, reason, physical, psychological, social, and sex education with exemplary methods, advice, habituation, attention, and punishment is very influential in forming religious character in the family environment.